Status of malnutrition among school children in selected schools of Quezon City implications to science education - Azizy, Mohammad Yusuf 1939- (1979)
This study on the status of malnutrition among school children sought to find out the extent of malnourishment among selected school children of Cubao and Kamuning elementary schools. The study was limited to 100 students, 7-10 years old. Data were gathered through the use of survey method and the questionnaire. The results of the study showed that physically, the malnourished students exhibited some signs like tiredness, pale lips, motor weakness, etc.; socially, the students had the tendency to become maladjusted and indifferent; mentally, students were inattentive and lacked curiosity. Teachers can help by teaching proper food habits and adequate nutrition to their students.
Vita.
Thesis (M.A. General Education)--University of the Philippines, Diliman.
Keywords: School children -- Nutrition -- Philippines -- Cubao (Quezon City); School children -- Nutrition -- Philippines -- Kamuning (Quezon City); Malnutrition -- Philipines -- Quezon City; Science -- Study and teaching (Elementary) -- Philippines -- Quezon City